Emergency remote teaching during covid-19 pandemic and undergraduates’ learning effectiveness at the university of Ibadan, Nigeria (2022)
The study investigated the influence of Emergency Remote Teaching (ERT) components (Zoom, Google Meet, Telegram forum, and LMS) on undergraduates’ learning effectiveness at the University of Ibadan. The descriptive survey research design was adopted and the population comprised 100 to 400 level students - with a sample size of 200 students who were randomly selected from the Faculties of Arts, Education and the Social Sciences. A 30- item questionnaire titled “Influence of ERT on Students’ Learning Effectiveness (IERTSLE)” was developed and validated by experts, and its reliability coefficient was 0.81 with the use of Cronbach alpha. Data were analyzed using descriptive and inferential statistics of frequency counts, simple percentages, analysis of variance (ANOVA), mean and standard deviation analysis at 0.05 level of significance. The findings of the study revealed that the ERT components (Zoom, Google Meet, Telegram Forum, and LMS) significantly influenced students’ Learning Effectiveness (F (4, 174) = 6.512; R2 = 0.13), and jointly accounted for 11.0% of its variance. Based on these findings, it was recommended that the Management of the University of Ibadan embark on full integration of online educational platforms to cater to both lecturers’ and students’ progressive skills and technical knowledge acquisition to help sustain them for the 21st century digital teaching and learning procedures. The study recommended that seminars, workshops, and other relevant programmes should be put in place to help improve students’ and lecturers’ adaptation to ERT teaching and learning in the institution.